Disaster Risk Reduction Based on Indigenous Knowledge in Fostering Environmental Care and Student Responsibility - Intansari, Ilfi; Saptono, Bambang; Sugara, Ujang; Wulandari, Sisca (PrimaryEdu : Journal of Primary Education, 2023)
The purpose of this study is 1) the application of indigenous Knowledge-based Disaster Risk Reduction education in fostering the character of environmental care and responsibility. 2) supporting and inhibiting factors in the implementation of indigenous Knowledge-based Disaster Risk Reduction education in fostering the character of environmental care and responsibility. This study is a qualitative research with a case study approach. This research data obtained from observation, documentation, and in-depth interviews. Data analysis used in this study is qualitative data analysis. The results of this study indicate: 1) the application of Disaster Risk Reduction education based on indigenous knowledge is very important in shaping the character of environmental care and responsibility of Elementary School students 1 Waymuli. 2) several supporting factors have an important role in supporting the successful formation of the character of environmental care and responsibility. Routine evaluation, especially in overcoming obstacles to the implementation of indigenous knowledge-based Disaster Risk Reduction education in fostering the character of environmental care and responsibility of Elementary School students 1 Waymuli Lampung